Preclinical evidence for the therapeutic value of TBX5 normalization in arrhythmia control - Rathjens, Franziska S.; Blenkle, Alica; Iyer, Lavanya M; Renger, Anke; Syeda, Fahima; Noack, Claudia; Jungmann, Andreas; Dewenter, Matthias; Toischer, Karl; El-Armouche, Ali; Müller, Oliver J.; Fabritz, Larissa; et al. (Cardiovascular research, 2021)
Arrhythmias and sudden cardiac death (SCD) occur commonly in patients with heart failure. We found T-box 5 (TBX5) dysregulated in ventricular myocardium from heart failure patients and thus we hypothesized that TBX5 reduction contributes to arrhythmia development in these patients. To understand the underlying mechanisms, we aimed to reveal the ventricular TBX5-dependent transcriptional network and further test the therapeutic potential of TBX5 level normalization in mice with documented arrhythmias.We used a mouse model of TBX5 conditional deletion in ventricular cardiomyocytes. Ventricular (v) TBX5 loss in mice resulted in mild cardiac dysfunction and arrhythmias and was associated with a high mortality rate (60%) due to SCD. Upon angiotensin stimulation, vTbx5KO mice showed exacerbated cardiac remodelling and dysfunction suggesting a cardioprotective role of TBX5. RNA-sequencing of a ventricular-specific TBX5KO mouse and TBX5 chromatin immunoprecipitation was used to dissect TBX5 transcriptional network in cardiac ventricular tissue. Overall, we identified 47 transcripts expressed under the control of TBX5, which may have contributed to the fatal arrhythmias in vTbx5KO mice. These included transcripts encoding for proteins implicated in cardiac conduction and contraction (Gja1, Kcnj5, Kcng2, Cacna1g, Chrm2), in cytoskeleton organization (Fstl4, Pdlim4, Emilin2, Cmya5), and cardiac protection upon stress (Fhl2, Gpr22, Fgf16). Interestingly, after TBX5 loss and arrhythmia development in vTbx5KO mice, TBX5 protein-level normalization by systemic adeno-associated-virus (AAV) 9 application, re-established TBX5-dependent transcriptome. Consequently, cardiac dysfunction was ameliorated and the propensity of arrhythmia occurrence was reduced.This study uncovers a novel cardioprotective role of TBX5 in the adult heart and provides preclinical evidence for the therapeutic value of TBX5 protein normalization in the control of arrhythmia.